Fasciculoventricular bypass tracts: Electrocardiographic and electrophysiologic features. Issue 3 (8th May 2020) - Asvestas, Dimitrios; Bazoukis, George; Mililis, Panagiotis; Dragasis, Stelios; Megarisiotou, Athanasia; Vlachos, Konstantinos; Sideris, Antonios; Efremidis, Michael; Letsas, Konstantinos P.
Abstract: Fasciculoventricular accessory pathways are rare variants of preexcitation. The differential diagnosis of fasciculoventricular accessory pathways from other preexcitation variants can be challenging. Based on two cases, we discuss the specific electrocardiographic and electrophysiologic features of fasciculoventricular bypass tracts. Abstract :